2014
DOI: 10.1186/gb-2014-15-2-r39
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequencing of the high oil crop sesame provides insight into oil biosynthesis

Abstract: BackgroundSesame, Sesamum indicum L., is considered the queen of oilseeds for its high oil content and quality, and is grown widely in tropical and subtropical areas as an important source of oil and protein. However, the molecular biology of sesame is largely unexplored.ResultsHere, we report a high-quality genome sequence of sesame assembled de novo with a contig N50 of 52.2 kb and a scaffold N50 of 2.1 Mb, containing an estimated 27,148 genes. The results reveal novel, independent whole genome duplication a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
311
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 275 publications
(329 citation statements)
references
References 64 publications
17
311
1
Order By: Relevance
“…This finding indicates that CNL genes adopted a gradual expansion strategy in the early stage of angiosperm evolution (from ;225 MYA as angiosperms diverged to around 100 MYA as asterids, rosids, and monocots diverged; Fig. 1; D 'Hont et al, 2012;Wang et al, 2014;Zeng et al, 2014). Intensive expansion of CNL genes seems to have occurred in the familial ancestors of Solanaceae and Poaceae, reaching hundreds of copies.…”
Section: The Three Nbs Classes Show Distinct Evolutionary Patterns Inmentioning
confidence: 98%
See 3 more Smart Citations
“…This finding indicates that CNL genes adopted a gradual expansion strategy in the early stage of angiosperm evolution (from ;225 MYA as angiosperms diverged to around 100 MYA as asterids, rosids, and monocots diverged; Fig. 1; D 'Hont et al, 2012;Wang et al, 2014;Zeng et al, 2014). Intensive expansion of CNL genes seems to have occurred in the familial ancestors of Solanaceae and Poaceae, reaching hundreds of copies.…”
Section: The Three Nbs Classes Show Distinct Evolutionary Patterns Inmentioning
confidence: 98%
“…Because the divergence of these angiosperm families occurred in the Paleogene and the divergence of their higher level taxonomies all occurred in the Cretaceous ( Fig. 1; Lavin et al, 2005;Stefanovic et al, 2009;D'Hont et al, 2012;Zhang et al, 2012;Peng et al, 2013;Yang et al, 2013;Kim et al, 2014;Wang et al, 2014;Zeng et al, 2014), the observed intensive expansion of NBS genes in angiosperms more likely coincided with the CretaceousPaleogene (K-P) boundary (;66 MYA). This finding suggests that different lineages of angiosperms either underwent a process to reinforce resistance or experienced increased selective pressure from environmental pathogens during this period.…”
Section: Differential Expansion During Angiosperm Evolution Shaped Tnmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the Lamiales, multiple WGD independent from the paleopolyploidy in the Solanales have been described: two or three in the lineage leading to U. gibba (one of which could be shared with M. guttatus) (18), and one in the lineage leading to S. indicum (estimated age similar to tomato) (19). This latter one and the oldest WGD in U. gibba could denote the same event, possibly even shared with the older WGD in the oleaster and ash lineage, or both could be independent ones, partly depending on their phylogenetic relationship (SI Appendix, section 3.2).…”
mentioning
confidence: 99%